Pengaruh Media Poster terhadap Pengetahuan dan Sikap Remaja tentang Kenakalan Remaja di SMA Negeri 8 Kota Jambi - Hanni Zahrani Shalsabilla; Adilla Solida; Muhammad Rifqi Azhary (Pusat riset dan Inovasi Nasional, 2025)
Adolescence is a crucial period in individual development, marked by significant physical, cognitive, and emotional changes. Juvenile delinquency is a concerning issue with broad implications for individuals, families, and society. This study aims to examine the effect of poster media on adolescents' knowledge and attitudes regarding juvenile delinquency at SMA Negeri 8 Kota Jambi. This study used a quasi-experimental design with a quantitative approach. The study sample consisted of 40 students of class X.1 selected by total sampling technique. Data were collected through questionnaires administered before and after the intervention. Data analysis was performed using a paired t-test to determine differences in the average scores of knowledge and attitudes before and after the intervention. The results showed a significant increase in students' knowledge and attitudes after being given poster media intervention. The average knowledge score increased from 11.15 to 17.65, and the average attitude score increased from 39.85 to 54.13. The paired t-test showed a significance value of 0.000 (p < 0.05) for both variables. Poster media is effective in increasing adolescents' knowledge and attitudes regarding juvenile delinquency. This study suggests that educational institutions can utilize poster media as an educational tool in juvenile delinquency prevention programs.